Migrant Labor and Temporary Work Agencies in the Case of Foxconn in the Czech Republic - Andrijasevic, Rutvica; Sacchetto, Devi (Lidé města, 2014)
The role of TWAs, whether formal or informal, has been commonly seen as connected to the demand for temporary and flexible labor determined especially by seasonal aspects of production. While this is certainly true and we could observe the fluctuation of migrant workers depending on production needs, what we would like to suggest is that the role of the agencies cannot be reduced to that of supplying workers based on just-in-time production. In the case of Foxconn the role of the TWA is not only a help to meet shortages or a form of probation, after which agency workers should be hired with direct contracts. Agency workers are a steady and fundamental part of the Foxconn workforce, with a strong labor turnover.